2022
DOI: 10.3390/ijms231810227
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1/FOXO Signaling Pathway in Breast Cancer Progression and Metastasis

Abstract: Breast cancer is the second most common cancer in women. The roles of the SIRT and FoxO proteins in tumor progression are known, but their roles in metastasis have not yet been clearly elucidated. In our study, we investigated the roles of SIRT and FoxO proteins their downstream pathways, proteins p21 and p53, in tumor progression and metastasis. We evaluated these proteins in vitro using metastatic 4TLM and 67NR cell lines, as well as their expression levels in tumor-bearing mice. In addition, the regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Extensive research indicates that the levels of SIRT1 are elevated in lung, liver, and colon cancers but decreased in pituitary and bladder tumours [50][51][52][53][54] . Despite controversies surrounding SIRT1's role as either a tumour promoter or suppressor, its overexpression has been consistently linked to improvements in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research indicates that the levels of SIRT1 are elevated in lung, liver, and colon cancers but decreased in pituitary and bladder tumours [50][51][52][53][54] . Despite controversies surrounding SIRT1's role as either a tumour promoter or suppressor, its overexpression has been consistently linked to improvements in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, no significant changes were found in the healthy epithelial cell line, MCF-10A, supporting our results describing its resistance to this treatment, at least at the doses used in this report. Recent studies investigated the dual effect of the SIRT1/FoxO1 axis as tumor promotor or suppressor in different cancers [ 58 ], and p53 has emerged as a downstream effector of this axis in BC [ 58 , 59 , 60 ]. Previous results showed that in the MCF-7 cell line, with p53 wild-type, the activation of SIRT1 promoted invasion and migration on malignant cells by inhibiting p53 [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SIRT1 signaling pathway plays a key role in the regulation of genes related to metastasis and stemness in BC [ 58 ]. In fact, Shi et al demonstrated that SIRT1-centered circuitry regulates CSCs origination, related to distant-metastasis and drug-resistance in BC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pliable agar, siomycin A had the capacity to slow down the development of cells independent of anchoring. Furthermore, siomycin A selectively induced apoptosis in metamorphosized cells but not in unmetamorphosed cells of similar origin [ 114 ]. Treatment with a cell-permeable ARF26-44 peptide (FOXM1 inhibitor) decreased angiogenesis and tumor cell development and caused a consequential escalation in cell death within the HCC region but not in the surrounding healthy liver tissue.…”
Section: Role Of Various Forkhead Boxes In Tumor Proliferation and Pr...mentioning
confidence: 99%